Animal crackers [videorecording (DVD)] - Sava, Scott Christian; Lorey, Dean; Sava, Scott Christian (Gravitas Ventures, 2023)
A family must use a magical box of animal crackers to save a run-down circus from bing taken over by their evil uncle Horatio P. Huntington.